2013
DOI: 10.1039/c3fo30301b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of citrus flavonoids, 5-hydroxy-3,6,7,8,3′,4′-hexamethoxyflavone and 3,5,6,7,8,3′,4′-heptamethoxyflavone, on the activities of macrophage scavenger receptors and the hepatic LDL receptor

Abstract: Epidemiological and animal studies point to a possible protective effect of citrus flavonoids against cardiovascular diseases. The aim of this study is to investigate the effects of citrus flavonoids, 5-hydroxy-3,6,7,8,3',4'-hexamethoxyflavone (5-OH-HxMF) and 3,5,6,7,8,3',4'-heptamethoxyflavone (HpMF), on the activities and expressions of macrophage scavenger receptors and the hepatic LDL receptor. Treatment of HpMF (20 μM) during THP-1 differentiation successfully attenuated 12-myristate 13-acetate (PMA)-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Wu et al suggested that heptaMF, but not 5‐demethylheptaMF, potently reduces phorbol 12‐myristate 13‐acetate (PMA)‐induced SR‐A mRNA expression and ox‐LDL uptake in THP‐1 monocytes during differentiation. However, 5‐demethylheptaMF was found to be more effective than heptaMF on ox‐LDL‐mediated CD36 and SR‐A expression in THP‐1‐derived macrophages, indicating that different mechanisms are involved in their anti‐atherogenic effects . In this study, the author also compared the inhibitory effect of heptaMF and 5‐demethylheptaMF with previously reported, nobiletin, 5‐demethylnobiletin, and 3′,4′‐didemethylnobiletin in the inhibition of ox‐LDL uptake in THP‐1‐derived macrophages, which showed 3′,4′‐didemethylnobiletin to be strongest one followed by 5‐demethylnobiletin and 5‐demethylheptaMF while nobiletin and heptaMF were the least active.…”
Section: Chemopreventive Effects Of Hydroxylated Pmfsmentioning
confidence: 81%
See 1 more Smart Citation
“…Wu et al suggested that heptaMF, but not 5‐demethylheptaMF, potently reduces phorbol 12‐myristate 13‐acetate (PMA)‐induced SR‐A mRNA expression and ox‐LDL uptake in THP‐1 monocytes during differentiation. However, 5‐demethylheptaMF was found to be more effective than heptaMF on ox‐LDL‐mediated CD36 and SR‐A expression in THP‐1‐derived macrophages, indicating that different mechanisms are involved in their anti‐atherogenic effects . In this study, the author also compared the inhibitory effect of heptaMF and 5‐demethylheptaMF with previously reported, nobiletin, 5‐demethylnobiletin, and 3′,4′‐didemethylnobiletin in the inhibition of ox‐LDL uptake in THP‐1‐derived macrophages, which showed 3′,4′‐didemethylnobiletin to be strongest one followed by 5‐demethylnobiletin and 5‐demethylheptaMF while nobiletin and heptaMF were the least active.…”
Section: Chemopreventive Effects Of Hydroxylated Pmfsmentioning
confidence: 81%
“…In this study, the author also compared the inhibitory effect of heptaMF and 5‐demethylheptaMF with previously reported, nobiletin, 5‐demethylnobiletin, and 3′,4′‐didemethylnobiletin in the inhibition of ox‐LDL uptake in THP‐1‐derived macrophages, which showed 3′,4′‐didemethylnobiletin to be strongest one followed by 5‐demethylnobiletin and 5‐demethylheptaMF while nobiletin and heptaMF were the least active. They further concluded that the 5‐hydroxyl group of PMF may play a vital role in the down‐regulation of SR activity in THP‐1 macrophages, although 3′,4′‐didemethylnobiletin was the most effective .…”
Section: Chemopreventive Effects Of Hydroxylated Pmfsmentioning
confidence: 99%
“…Considering both clinical and experimental considerations, we opted for single-dose intravenous administration, as well as singleand multiple-dose intragastric administration. Previous reports have indicated the presence of a 5-O-glucuronide metabolite of wogonin in SD rats, affirming the reactivity of the 5-OH group in flavonoids (Kou et al, 2013). Given that GL-V9 features a 5-OH group in its structure, the possibility of glucuronide conjugation, if it occurs, may involve this position.…”
Section: Discussionmentioning
confidence: 67%
“…Flavonoids from citrus did not affect CD36 mRNA expression in the monocyte‐like cell line THP‐1. Interestingly, one of these flavonoids reduced oxLDL uptake through a reduction in class A scavenger receptor SR‐A expression . Furthermore, the expression of class B scavenger receptor SRB1 in rat livers was indirectly reduced by an estrogen‐dependent increase in LDLR activity , which could be a mechanism for potential estrogenic IF effects on CD36.…”
Section: Discussionmentioning
confidence: 99%